Pharmacokinetics and safety of tiotropium+olodaterol 5 μg/5 μg fixed-dose combination in Chinese patients with COPD. (August 2020) - Wang, Zhenlei; Tadayasu, Yusuke; Hu, Na; Shu, Shiqing; Hu, Chao; Luo, Zhu
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is one of the major causes of morbidity and mortality worldwide and in China. For patients with more severe symptoms, initial treatment with long acting β2-agonists and long-acting muscarinic antagonists combination therapy is recommended. Tiotropium + olodaterol fixed-dose combination (Tio + Olo FDC) is an aqueous solution of tiotropium bromide and olodaterol delivered by the RESPIMAT® Soft Mist™ inhaler for patients with moderate to very severe COPD. Methods: This single site, open-label, phase Ib clinical study assessed the pharmacokinetic (PK) and safety profiles of once-daily Tio + Olo FDC (5 μg/5 μg) after single dose and at steady state in Chinese patients with moderate to severe COPD over 3 weeks. The PK and safety profiles of Japanese and Caucasian populations from 2 independent COPD studies were provided for comparison. Results: A total of 12 Chinese patients received Tio + Olo FDC. After multiple inhaled administration of Tio + Olo FDC, tiotropium and olodaterol were rapidly absorbed and reached peak plasma concentration at about 5 and 25 min, respectively. The accumulation ratios after multiple administrations were 1.3 and 1.6 for tiotropium and olodaterol in Chinese patients. Tio + Olo FDC was well-tolerated; all AEs were mild. Conclusion: Tio + Olo FDC (5 μg/5 μg) was rapidly absorbed and had a good safety profile in Chinese patients with COPD.